(3QSGdI GdEjbGX hGdHTGQI dCgd GdZadI hGdMb hGdWgGQIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce GdefRg Yf ehgeGJ GdYOe GdedHhS hJhSdJ Edjg Hhdjg bGFe GdOjf GdeWdY Ydi SQGFQ GdYbhd hGdfahS s
(3BNQgG (B:s
(3ef bUQ GdYbhd GdUGajI hLYdgG deHOYg UaI hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B56s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds